Corporate Knights (JSTOR)
Corporate Knights, the award-winning magazine for clean capitalism, was founded in 2002 and is published four times per year as an insert in the Globe and Mail (Canada) and Washington Post. As one of the world's largest circulation (125K+) magazines focused on the intersection of business and society, CK is the most prominent brand in the clean capitalism media space.
Keywords: Business, Business & Economics, Economics, Management & Organizational Behavior